Special and Inclusive Teachers’ Experience in The Distance Learning - Ensao, Riza B.; S. Manhilot, Lance Patrick; Paghacian, Heaven; Plania, Kimberly; Rago, Kaye Allison; Viovicente, Fiona M. (International Journal of Humanities and Education Development (IJHED), 2022)
This study was designed to explore the lived experiences of special and inclusive teachers in distance learning and gained necessary perspective about their different experiences and challenges in the new normal education in distance learning. It utilized the use of phenomenological research design and simple random sampling on choosing the participants. Data were analyzed through thematic analysis method. The results indicated that the teachers felt inadequately prepared to teach atypical learners in distance learning because of some factors, examples are lack of resources of teachers and students. Almost all participants indicated that they discovered their own teaching strategies in handling atypical learners. In addition, the teachers make use of the available technology by utilizing different educational applications. Also, the majority of the teachers motivate their students to continue to learn in the new normal. Implications of these results are discussed.